Asymmetry reversals and the business cycle - Roberta Distante; Ivan Petrella; Emiliano Santoro (Fondazione Eni Enrico Mattei (FEEM), 2013)
The cross-sectional dynamics of the U.S. business cycle is examined through the lens of quantile regression models. Conditioning the quantiles of firm-level growth to different measures of technological change highlights a deep connection between counter-cyclical skewness and the transmission of aggregate disturbances. Asymmetry reversals emerge as the dominant source of cyclical variation in the probability density, generating a powerful amplification of aggregate shocks to firm technology. Designing and validating heterogeneous firm business cycle models should necessarily account for this empirical finding.
Keywords: C21; E32; 330; Corporate Growth; Conditional Quantiles; Business Cycles; Asymmetry Reversals